1992
DOI: 10.1034/j.1600-0501.1992.030306.x
|View full text |Cite
|
Sign up to set email alerts
|

Healing‐in of root analogue titanium implants placed in extraction sockets. An experimental study in the beagle dog.

Abstract: The aim of these animal experiments was to characterize and evaluate the healing-in of root analogue titanium implants fitting with high precision to the alveolar wall. Four beagle dogs were used in the study. The roots of the 3rd and 4th mandibular premolars in both quadrants of 3 dogs and in 1 quadrant of 1 dog (dog 4) were extracted after hemisection. Each root was machine-copied to 1 titanium analogue. In dog 4, however, 2 titanium analogues were fabricated from each of the 4 extracted roots. This enabled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 0 publications
1
72
0
1
Order By: Relevance
“…The polymethacrylate tooth-analogue was encapsulated by soft tissue rather than osseointegrated 1 . Animal studies with root-identical titanium implants yielded extremely favourable results with clear evidence of osseointegration 4 . In several instances implant insertion led to fractures of the thin buccal wall of the alveolar bone 3,4 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The polymethacrylate tooth-analogue was encapsulated by soft tissue rather than osseointegrated 1 . Animal studies with root-identical titanium implants yielded extremely favourable results with clear evidence of osseointegration 4 . In several instances implant insertion led to fractures of the thin buccal wall of the alveolar bone 3,4 .…”
Section: Discussionmentioning
confidence: 98%
“…Perfect implant fit could lead to excellent primary stability, however, it might be responsible for the intermediate term failure, because of the subsequent uniform pressure-induced resorption concerning the entire alveolar surface 4,8,9 simultaneously affecting the thin buccal layer, which is prone to fracture and pressure-induced resorption 4,8,9 .…”
mentioning
confidence: 98%
“…Ancak çekilen diĢle aynı morfolojiye sahip kiĢiye özgü bir implantın çekim soketine yerleĢtirilmesi ile implant ve soket arasındaki Ģekil uyumsuzluğu ortadan kaldırılabilir dolayısıyla kemik grefti, membran ve kemik frezlerinin kullanılmasına da gerek kalmayacaktır ve bu sayede cerrahi prosedür de kolaylaĢabilir. [6][7][8][9][10][11][12][13] Bazı rezidüel kretler ise oldukça incedir ve standart çapta kök Ģekilli implantlar yerleĢtirildiğinde, implant çevresinde yaklaĢık 1-2 mm'lik çevresel kemik kalmamaktadır.…”
Section: öZunclassified
“…The ideal implant placement would be in contact with the socket without putting undue pressure on the socket walls, with the exception of where there is a very thick alveolar plate that leaves no gap between the head or neck of the implant and surrounding socket walls (Kohal et al, 1997). Some studies have shown that close adaptation of the implant to the socket wall promotes greater osseos integration (Lundgren et al, 1992;Wilson et al, 1998).…”
Section: Introductionmentioning
confidence: 97%